Counseling on making learning videos with mobile phones to Indonesian educators - Ratnadewi, Ratnadewi; Sartika, Erwani Merry; Wahono, Sri; Amadeus, Clarence (Community Empowerment, 2021)
Education sector in Indonesia was shocked by the total change from the previously offline-based education system to online, due to the state of the Covid-19 pandemic. No country wants to experience this pandemic, but the rapid spread has changed all sectors of life, especially the education in Indonesia. Educators are required to continue to carry out online learning activities, but not all educators can create learning video content. Moving on from this problem, an online quick education was made to make learning videos using mobile phones, which was organized by Maranatha Christian University in collaboration with Guru Mengajar untuk Nusantara and STKIP PGRI Trenggalek. The material given was flyer design techniques, photo taking techniques, and making videos with Kinemaster. The postermywall and kinemaster applications used can be downloaded on the playstore on android. The activity was open to teachers and lecturers for free and guided for one month. Participants who registered were 1059 people from various district in Indonesia and were guided by 39 instructors. At the end of the activity, 510 participants (48.16%) passed with the criteria of being able to make learning videos until they were uploaded to YouTube.